The relationship between emotional intelligence and occupational performance among librarians in public libraries, Malaysia / Mad Khir Johari Abdullah Sani - Abdullah Sani, Mad Khir Johari (2013)
This thesis reports the relationship between Emotional Intelligence (El) and Occupational Performance (OP) of Malaysian Public Librarians (MPLibs). Public librarians are important assets since they are social agents that advocate a knowledge society development in Malaysia. As employees in service organizations, they are expected to be highly dynamic and provide quality services. These jobs involve understanding, communicating, empathizing with and learning from other members working in the organizations. These skills require not only a high degree of intellectual ability but a high level of El. El, therefore, seems to be considered essential for library employees understand other people’s feelings and for them to be involved in a relationship that will facilitate successful management and performance. This research employs a sequential exploratory mixed-method through semi structured interviews followed by a survey. Phase one of the preliminary study explored the librarians’ experiences and perceptions pertaining to El through face-to-face interviews. Fourteen senior public librarians informed this phase of the study. The qualitative data were transcribed and coded based on Predetermined Concept Choice Mapping data analysis to refine and ascertain research model, variables, hypotheses and El dimensions. 20 El dimensions including 2 new dimensions were found and applied by MPLibs and help develop Public Librarian Emotional Intelligence Questionnaire (PubLIBEIQ). The PubLIBEIQ was then used as an instrument in a quantitative cross sectional survey (phase two) to identify the level of El, and to test the relationship between El and job satisfaction (JS) and job commitment (JC) of OP of 180 respondents. Descriptive findings showed a high level of El among MPLibs, where the mean value was in the range of 5.026 to 6.546 on a 7-point Likert. The results of the correlation and regression analyses suggest that all formulated hypotheses were supported. On the other hand, the conceptualized determinants and impacts of OP specifically JS and JC were validated and substantiated. Further analysis involving multiple regression revealed that the strongest predictors of JS are self management and relationship management while self awareness, self management and social awareness are the strongest predictors of JC. Consequently, it is recommended that public libraries develop training programs in order to enhance the El of librarians and employees in libraries. Theoretical contribution of the research includes development of a theoretical model of self awareness, self management, social awareness and relationship management of El and an OP framework of MPLibs. Practically, the research reveals the El competencies which are imperative to contribute the performance of MPLibs. Methodologically, the research illustrates the effective use of the mixed-method approach within the pragmatic research paradigm. The incorporation of face-to-face interview combines subjectivity and objectivity of the problem situation [phenomenon] thus gives a rich understanding of El within the context of a public service agency in Malaysia.